2020
DOI: 10.1002/asia.202000482
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Macrocyclic Dysoxylactam A

Abstract: The total synthesis of dysoxylactam A, a novel 17‐membered macrolactam with potent multi‐drug‐resistant reversing activities, has been achieved, starting from 4‐pentene‐1‐al in a longest linear sequence of 17 steps and 9.5% overall yield. The key transformations consist of iterative aldol and ring‐closing metathesis reactions for the construction of the stereochemically enriched polypropionate scaffold and the macrocycle, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…With the alcohol 3 in hand, we explored the esterification of the hindered secondary alcohol with N ‐Boc‐ l ‐valine. Such esterifications are notoriously difficult, [15] with this step being highlighted as problematic in previous syntheses of dysoxylactam A; [2–4] which was our experience too. Using a modification of Chandankar's DCC/DMAP conditions, we obtained the desired ester 8 in moderate yield, but with a significant amount of epimerisation [2] .…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…With the alcohol 3 in hand, we explored the esterification of the hindered secondary alcohol with N ‐Boc‐ l ‐valine. Such esterifications are notoriously difficult, [15] with this step being highlighted as problematic in previous syntheses of dysoxylactam A; [2–4] which was our experience too. Using a modification of Chandankar's DCC/DMAP conditions, we obtained the desired ester 8 in moderate yield, but with a significant amount of epimerisation [2] .…”
Section: Figurementioning
confidence: 89%
“…Ye's synthesis [3] comprised 15 steps installing the stereochemistry using an Aggarwal homologation and Brown and Krische allylations, with the macrocycle being constructed using a ring‐closing metathesis. The third synthesis of dysoxylactam A was reported by Yu in 17 steps, [4] using diastereoselective aldol and alkylation chemistry utilising Evans‐type auxiliaries, with the macrocycle being constructed again by ring‐closing metathesis.…”
Section: Figurementioning
confidence: 99%
“…: [ 13 ] –3.6 ( c 1.0, CHCl 3 ); Yu et al . : [ 14 ] –14.1 ( c 0.5, CHCl 3 ); Aggarwal et al . : [ 15 ] –8.0 (c 1.0, CHCl 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The key steps included iterative Evans aldol and ring‐closing metathesis reactions. [ 14 ] Quite recently, Aggarwal and coworkers completed the fourth total synthesis of 1 in 11 steps with about 4.9% overall yield by using iterative lithiation‐borylation reactions as the key C—C bond‐forming and stereo controlling steps. [ 15 ] These synthetic efforts demonstrated that the construction of the…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…A macrolactam named dysoxylactam A, isolated from the bark of Dysoxylum hongkongense, was found to hold the ability to reverse multidrug resistance in cancer cells and inhibit the function of P-glycoprotein, a key mediator in multidrug resistance. 45 In 2020, Reddy and Yu established a total synthesis of dysoxylactam A (212) using RCM as its key step (Scheme 23). 45 The process advanced with the preparation of the polypropionate fragment 209 being achieved in a stereocontrolled manner through 10 sequential reactions from commercially available pent-4-enal…”
Section: Review Synopenmentioning
confidence: 99%